Are we Nearly There Yet? A Desires & Realities Framework for Europe’s AI Strategy - Polyviou, Ariana; Zamani, Efpraxia D. (My University, 2023)
Of all emerging technologies, Artificial Intelligence (AI) is perhaps the most debated topic in contemporary society because it promises to redefine and disrupt several sectors. At the same time, AI poses challenges for policymakers and decision-makers, particularly regarding formulating strategies and regulations to address their stakeholders’ needs and perceptions. This paper explores stakeholder perceptions as expressed through their participation in the formulation of Europe’s AI strategy and sheds light on the challenges of AI in Europe and the expectations for the future. Our analysis reveals six dimensions towards an AI strategy; ecosystems, education, liability, data availability sufficiency & protection, governance and autonomy. It draws on these dimensions to construct a desires-realities framework for AI strategy in Europe and provide a research agenda for addressing existing realities. Our findings contribute to understanding stakeholder desires on AI and hold important implications for research, practice and policymaking.
Keywords: AI ethics; AI strategy; Artificial Intelligence; Technology policy; Technology regulation